Storm Tide and Wave Simulations and Assessment II - Hsiao, Shih-Chun; Chiang, Wen-Son; Chen, Wei-Bo (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Storm tides, surges, and waves associated with typhoons/tropical cyclones/hurricanes are the most severe threats to coastal zones, nearshore waters, and navigational safety. Therefore, predicting typhoon/tropical cyclone/hurricane-induced storm tides, surges, waves, and coastal erosion is essential for reducing the loss of human life and property and mitigating coastal disasters. There is still a growing demand for novel techniques that could be adopted to resolve the complex physical processes of storm tides, surges, waves, and coastal erosion, even if many studies on the hindcasting/prediction/forecasting of typhoon-driven storm tides, surges, waves, and also morphology evolution have been carried out through numerical models in the last decade. This Special Issue intends to collect the latest studies on storm tide, surge, and wave modeling and analysis utilizing dynamic and statistical models and artificial intelligence approaches to improve our simulating and analytic capabilities and our understanding of storm tides, surges, and waves. Five high-quality papers have been accepted for publication in this Special Issue; these papers cover the application and development of many high-end techniques for storm tides, surges, waves, and on-site investigation of coastal erosion and accretion.